1996
DOI: 10.1007/bf01712235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapid permissive hypercapnia on hemodynamics, gas exchange, and oxygen transport and consumption during mechanical ventilation for the acute respiratory distress syndrome

Abstract: These data indicate that acute hypercapnia increases DO2 and O2 off-loading capacity in ARDS patients with normal plasma lactate, without increasing O2 extraction. Whether this would be beneficial in patients with elevated lactate levels, indicating tissue hypoxia, remains to be determined. Furthermore, even though hypercapnia was well tolerated, the increase in Qva/Qt, CI, and MPAP should prompt caution in patients with severe hypoxemia, as well as in those with depressed cardiac function and/or severe pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
2
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 36 publications
9
41
2
6
Order By: Relevance
“…Consistent with our findings, an increase of right ventricular end-diastolic volume, right ventricular ejection fraction and CI has been demonstrated recently during APRV with spontaneous breathing in patients with ALI [16]. A marked increase in HR and CI at unchanged SVI, ITBVI and CVP tm , found during APRV without spontaneous breathing at the same Paw limits when compared to APRV with spontaneous breathing, may be attributed to hypercapnia and respiratory acidosis [25,26,27,28,29]. Compatible with these investigations [25,26,27,28,29], an increase in CI during permissive hypercapnia was associated with decreased systemic vascular resistance, reflecting systemic vasodilation, which effected no change in MAP in our patients.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with our findings, an increase of right ventricular end-diastolic volume, right ventricular ejection fraction and CI has been demonstrated recently during APRV with spontaneous breathing in patients with ALI [16]. A marked increase in HR and CI at unchanged SVI, ITBVI and CVP tm , found during APRV without spontaneous breathing at the same Paw limits when compared to APRV with spontaneous breathing, may be attributed to hypercapnia and respiratory acidosis [25,26,27,28,29]. Compatible with these investigations [25,26,27,28,29], an increase in CI during permissive hypercapnia was associated with decreased systemic vascular resistance, reflecting systemic vasodilation, which effected no change in MAP in our patients.…”
Section: Discussionsupporting
confidence: 78%
“…In both animal models and human studies, modest hypercapnia has been shown to have reproducible hemodynamic effects that are well tolerated and reversible [88] . In both canine and human studies, these effects have included a decrease in systemic vascular resistance (systemic vasodilation), and increased cardiac output despite a decrease in cardiac contractility [89][90][91] , although these findings are not consistent in all studies [92] . One human study evaluated the effects of buffer therapy on hypercapnic acidosis.…”
Section: Clinical Effects Of Permissive Hypercapniamentioning
confidence: 79%
“…Nevertheless, the arterial CO 2 tension in the low rate, high PEEP group was systematically greater than the arterial CO 2 tension in the high rate, low PEEP group. Increased arterial CO 2 levels, however, are associated with increased cardiac output, a result of catecholamine release and systemic vasodilation (51,55,67). If any effect would be expected from the difference in Pa CO 2 between the two strategies, it would be to increase the cardiac output in the low rate, high PEEP group.…”
Section: Discussionmentioning
confidence: 99%